MUI Fatwa No. 10 of 2008 on Siri Marriage: An Interdisciplinary Study from the Perspective of Maqashid Sharia - Kalijunjung Hasibuan; Syamruddin Nasution; Salmaini Yeli (Syura: Journal of Law, 2026)
This study investigates the implementation of MUI Fatwa No. 10 of 2008 concerning underhand marriage (nikah siri) in Padang Lawas Regency through an interdisciplinary maqāṣid al-syarī‘ah perspective. The persistence of underhand marriage remains a significant legal and social problem because many communities regard it as religiously valid despite the absence of formal state recognition, resulting in legal vulnerabilities for women and children. This study aims to examine the implementation of the fatwa, identify legal and social obstacles, explore the effectiveness of an interdisciplinary approach in addressing family law issues, and analyze the phenomenon through the framework of maqāṣid al-syarī‘ah. Employing a qualitative field research design, data were collected through interviews, observations, and documentation, and analyzed using a phenomenological approach involving epoche, phenomenological reduction, meaning categorization, textual and structural descriptions, and synthesis of meaning. The findings reveal that the implementation of the fatwa has not been fully effective due to weak legal enforcement, limited public legal awareness, cultural traditions, and economic considerations. The study further demonstrates that integrating legal, religious, social, cultural, and economic perspectives provides a more comprehensive understanding of underhand marriage. This research contributes to the development of interdisciplinary Islamic family law studies by strengthening the application of maqāṣid al-syarī‘ah as a holistic framework for resolving contemporary family law challenges in Muslim societies.